2001
DOI: 10.1016/s0378-4320(01)00102-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and ultrastructural changes occurring during degeneration of goat preantral follicles preserved in vitro

Abstract: The present work has investigated the morphological and ultrastructural changes occurring during degeneration of goat preantral follicles preserved in vitro and showed quantitative data about the distribution of follicular degeneration types in the control and after preservation in coconut water solution or Braun-Collins solution at different temperatures (4, 20 or 39°C) and incubation times (4, 12 or 24 h). At the slaughterhouse, the pair of ovaries of each animal was divided into 19 fragments. One ovarian fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 29 publications
3
27
0
1
Order By: Relevance
“…Silva et al (2001) observed that the damage to mitochondria is one of the first signs of degeneration in goat preantral follicles during storage in vitro. Ischemia impairs cellular energetic metabolism which decreases the activity of the Na+/K+-ATPase pump with a gain in sodium (Bonz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al (2001) observed that the damage to mitochondria is one of the first signs of degeneration in goat preantral follicles during storage in vitro. Ischemia impairs cellular energetic metabolism which decreases the activity of the Na+/K+-ATPase pump with a gain in sodium (Bonz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These vacuoles represent endoplasmic reticulum swelling (Hay et al, 1976), or altered mitochondria (Fuku et al, 1995). Silva et al (2001) reported that mitochondria exhibiting extensive swelling and disappearance of most of cristae as well as endoplasmic reticulum enlarged in volume are the first sign of degeneration in preantral follicles. The low density of granulosa cells recorded in Type 2 degenerated follicles may be due to their enlarged volume.…”
Section: Discussionmentioning
confidence: 99%
“…After fixation, specimens were rinsed in the buffer and post-fixed in 1% osmium tetroxide, 0.8% potassium ferricyanide and 5 mM CaCl2 in a 0.1 M sodium cacodylate buffer (Silva et al, 2001). Subsequently, the samples were dehydrated in acetone and embedded in Spurr's epoxy resin.…”
Section: Methodsmentioning
confidence: 99%
“…According DRIANCOURT & THUEL (1998) the oocyte is the first cell within the follicle to be affected by atresia, and whether oocyte atresia is related to oocyte defects or to an improper dialogue between the oocyte and its surrounding granulosa cells remains unclear. In addition, we show in previous study that the oocyte of goat preantral follicles were more sensitive to degeneration than granulosa cells (SILVA et al, 2001). In contrast, in both solutions after preservation at 39 o C for 12h and 24h, there were significantly higher percentage of primordial follicles with degenerated oocyte and granulosa cells, i.e., Type 2 degeneration.…”
Section: Discussionmentioning
confidence: 56%